Flat puppets on an empty screen, stories in the round; Imagining space in "wayang kulit" and the worlds beyond - Arps, Bernard (Wacana, Journal of the Humanities of Indonesia, 2016)
The puppets are flat, the screen against which they are placed and moved is white and devoid of scenery. In what kinds of space do the stories of the classical shadow-play of Java, Bali, Lombok, and the Malay world unfold despite this double flatness? How do performers use not only puppets and screen but also music and language to bring space into being? What must spectators know and do to make sense of these storytelling techniques? As a contribution to the narratological study of the multimodal making of storyworlds, I demonstrate that wayang kulit caters for different degrees of interpretive competence, which yield different understandings of the space that wayang portrays. An expert way of apprehending space requires seeing beyond the screen, puppets, and silhouettes, or even looking away from them. At the same time the peculiar ways of narrating space in wayang point to a deeply felt spatiality in real-life contexts as well.